Heavy metal contamination in the sediment and plants of the Sundarbans, India - Kader, Abdul; Narayan Sinha, Sankar (Chemistry and ecology, 2018)
Heavy metals are one of the hazardous contaminants in the total environment. The present study shows that the Sundarbans soil is contaminated with sludge and moderately contaminated with Cd and Co according to Contamination factor (CF), Enrichment factor (EF), Index of geo-accumulation (Igeo), and Ecological risk factor (ERF). The correlation, principle component analysis and factor analysis showed that Mn and Fe might have lithogenic origin whereas Cu, Pb, Co and Cd have anthropogenic inputs. The screening quick reference table (SQuiRT) shows that Cu and Cd may exert a possible toxic effect on the sediment dwelling biota. The phytoremediation study revealed that the endangered Heritiera fomes leaves can accumulate 80% of cadmium from the soil, which is highest based on this study as compared to other mangroves. The study also indicated that threatened date palm Phoenix paludosa leaves can accumulate 74% and 73% of Cu and Fe, respectively, from the soil. Now a day, there has been a spurt in mangrove plantations worldwide for the conservation of mangrove ecosystem using ecological engineering approaches. The present study is very much useful to choose a proper plant to decontaminate the soil from various heavy metal pollutants for effective management of mangrove wetlands.